School-based mindfulness intervention for depressive symptoms in adolescence: For whom is it most effective? - Saarinen Aino; Hintsanen Mirka; Vahlberg Tero; Hankonen Nelli; Volanen Salla-Maarit (WILEY, 2025)
Introduction: There is accumulating evidence for the effectiveness of mindfulness-based interventions in alleviating depressive symptoms. A crucial question is, however, whether mindfulness interventions are more effective for some individuals than others, depending on individual characteristics before a mindfulness intervention. We exploratorily investigated whether the effectiveness of school-based mindfulness intervention against depressive symptoms is modified by executive functions, rumination, and emotion regulation among adolescents.
Methods: The longitudinal data included adolescents with at least mild depressive symptoms at the baseline (n = 369, at the 6th-8th grade, 68.4% female) who were randomized into a 9-week school-based mindfulness intervention group, into an active control group receiving relaxation program, or into an inactive control group. Adolescents' executive functions, rumination, and emotion regulation (i.e., acceptance, catastrophizing, and positive reappraisal) were assessed at the baseline; and depressive symptoms at three time points (at the baseline and at 9-week and 6-month follow-ups).
Results and Conclusions: In adolescents with at least mild depressive symptoms at the baseline, high catastrophizing, high acceptance, and low executive functions were found to increase the effectiveness of mindfulness-based intervention against depressive symptoms. There seemed to be some sex differences. Thus, when aiming to alleviate depressive symptoms, mindfulness-based intervention may possibly be more effective for adolescents with high catastrophizing, high acceptance, and low executive functioning (than for adolescents with the opposite dispositions). However, as this study was exploratory by nature and corrections for multiple testing were not used, the findings must be regarded as preliminary and need confirmation in further studies.